Forever is Always Finite: Reflections on Radical Life Extension. Issue 2 (3rd April 2019) - Anderson, Herbert
ABSTRACT: This essay reflects on the Radical Life Extension movement from six critical perspectives: RLE (1) ignores the benefits of finitude; (2) perpetuates the denial of death by seeking to vanquish it; (3) disregards the paradoxical nature of death as problem and mystery; (4) turns death and the Bronze Dream into idols; (5) overlooks a plethora of ethical dilemmas; and (6) fails to ask the central life question: "how well can we live?." RLE is not only problematic: it is redundant. Being kept in the love of God forever is a different kind of 'radical life extension' that includes finitude and death.